2014
DOI: 10.4028/www.scientific.net/msf.803.16
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Recycled Glass Waste as Partial Replacement of Fine Aggregate in Concrete Production

Abstract: Glass dust waste creates chronic environmental problems, mainly due to the inconsistency of waste glass streams. Glass is widely used in our lives through manufactured products such as sheet glass, bottles, glassware, and vacuum tubing. Glass is an ideal material for recycling. The use of recycled glass helps in energy saving. The increasing awareness of glass recycling speeds up inspections on the use of waste glass with different forms in various fields. One of its significant contributions is to the constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 5 publications
0
9
0
3
Order By: Relevance
“…Ibrahim (2017) showed that it was possible to use glass waste as a partial substitute of sand up to 40% by weight without reducing the tensile and compressive strengths compared to the control concrete, and the best replacement dose was 15%. Rahim et al (2015) found that the best value of the compressive strength is obtained in the mixture containing 10% of glass waste as a replacement of fine aggregate, which represents an increase of 13.6% compared to the control concrete, as shown in the Table 1. Abdallah and Fan (2014) showed a continuous increase in flexural strength with age when replacing fine aggregate by glass waste.…”
Section: Introductionmentioning
confidence: 88%
“…Ibrahim (2017) showed that it was possible to use glass waste as a partial substitute of sand up to 40% by weight without reducing the tensile and compressive strengths compared to the control concrete, and the best replacement dose was 15%. Rahim et al (2015) found that the best value of the compressive strength is obtained in the mixture containing 10% of glass waste as a replacement of fine aggregate, which represents an increase of 13.6% compared to the control concrete, as shown in the Table 1. Abdallah and Fan (2014) showed a continuous increase in flexural strength with age when replacing fine aggregate by glass waste.…”
Section: Introductionmentioning
confidence: 88%
“…The compressive strength of a material is defined by the capacity of the material to resist defects in the form of fractures. Compressive strength as a function of the concrete relies on many factors linked to consistency, mixing nature, and quality management of the products used in concrete construction (Rahim et al, 2015). The compression testing machine is shown in Fig.…”
Section: Compressive Strengthmentioning
confidence: 99%
“…Beberapa peneliti melaporkan bahwa semen dapat digunakan sebagai penganti sebagian semen ( Du and Tan 2014;Islam, et al 2017;Tamanna et al P-ISSN 2088-0561 E-ISSN 2502-1680 2016; Tamanna and Tuladhar 2020). Beberapa peneliti seperti Ali and Al-Tersawy (2012); Ganiron (2013); Aswad and Soeparyanto (2014); Ganiron (2014); Sadoon and Fan (2014); Rahim et al (2015); Adaway and Wang (2015); Ogundairo et al (2019); Seddik Meddah (2019) Małek et al (2020) memanfaatkan pecahan limbah kaca sebagai penganti sebagian agregat halus dan melaporkan bahwa limbah kaca cukup baik digunakan dalam mengganti sebagian agregat halus dan menambah kuat tekan beton dengan variasi tertentu. Tujuan penelitian ini adalah menganalisis pengaruh pengantian sebagian agregat halus dengan limbah kaca (botol kaca) terhadap kuat tekan beton.…”
Section: Latar Belakangunclassified
“…Variasi Limbah Kaca Beton dengan menggunakan limbah kaca juga memiliki kuat tekan beton karakteristik yang jauh berkurang apabila dibandingkan dengan kuat tekan beton karakteristik beton normal (Gambar 2). Hal ini menjelaskan bahwa limbah kaca hanya bisa digunakan dengan variasi maksimal <40% limbah kaca, karena dapat melebihi kuat tekan beton rencana akan tetapi berkurang jika dibandingkan dengan kuat tekan rata-rata beton normal dan kuat tekan beton karakteritik beton Rahim et al (2015) berpendapat jumlah limbah kaca yang lebih tinggi menyebabkan penurunan daya serap air dan melemahnya kuat tekan beton. Limbah debu kaca tidak memiliki karakteristik kering permukaan jenuh (SSD) dan hal ini akan menyebabkan penurunan kuat tekan bila terdapat kelebihan air pada beton.…”
Section: Gambar 2 Perbandingan Uji Kuat Tekan Beton Karakteristik Untuk Berbagaiunclassified
See 1 more Smart Citation